The parasite Parvilucifera infectans kills the harmful alga Alexandrium minutum under different salinities and disrupts PSP toxin production - Ruchicka Annie O’Niel; Muhaiminatul Azizah; Georg Pohnert; Marine Vallet (Harmful Algae, 2026)

Correction to: Epigenetic Regulation Links Bacterial Signaling to Growth and Reproductive Development in the Green Macroalga Ulva compressa (Chlorophyta) - Janine F. M. Otto; Hermann Holbl; Nico Ueberschaar; Georg Pohnert; Thomas Wichard (Marine Biotechnology, 2026)

Epigenetic Regulation Links Bacterial Signaling to Growth and Reproductive Development in the Green Macroalga Ulva compressa (Chlorophyta) - Janine F. M. Otto; Hermann Holbl; Nico Ueberschaar; Georg Pohnert; Thomas Wichard (Marine Biotechnology, 2026)

Heat-Induced metabolomic shifts in cold-adapted Ulva holobiont from Antarctica (Potter Cove, South Shetland Islands) - Marine Vallet; Fatemeh Ghaderiardakani; Maria Liliana Quartino; Filip Kaftan; Georg Pohnert; Thomas Wichard (Journal of Applied Phycology, 2026)
The algal holobiont, a symbiotic association of algae and bacteria, provides strategies to cope with environmental stresses. Bacteria associated with the green alga Ulva (Chlorophyta) are known to produce essential bioactive compounds, such as thallusin and ectoine, that promote algal growth; however, the metabolic mechanisms underlying stress adaptation in these mutualistic interactions remain poorly understood. Specifically, research is still emerging on the metabolome of cold-adapted Ulva holobionts from remote regions, such as Antarctica, and on how the metabolic profiles respond to environmental changes. This study thus examined heat-induced changes in osmolyte and zwitterion molecules bearing balanced positive and negative charges in Ulva sp. (strain FSU-UPC-109) collected from the Antarctic ecosystem of Potter Cove, South Shetland Islands, and maintained under laboratory conditions at 2°C. Using ultra-high-performance liquid chromatography coupled with high-resolution mass spectrometry (UHPLC–HRMS), we identified highly polar low molecular weight compounds, including cysteinolic acid, ectoine, glutamine, glycerol, and proline. Their spatial distribution on the thallus and rhizoids was determined with atmospheric-pressure matrix-assisted laser desorption/ionization imaging (AP–SMALDI). We demonstrated that the metabolite levels shifted significantly under heat stress, indicating that environmental temperature changes strongly influence the metabolome of Antarctic Ulva seaweed and may support their capacity for thermal acclimation. Graphical abstract Using high-resolution (imaging) mass spectrometry, we studied the heat-induced changes in abundance of the osmolytes and zwitterions, molecules bearing balanced positive and negative charges, in Ulva collected from the Antarctic ecosystem of Potter Cove, South Shetland Islands.

Insights from an integrated multi-omics analysis: The synergistic effect of arginine and urea in marine diatom Phaeodactylum tricornutum - Yu Li; Runqing Yang; Georg Pohnert; Dong Wei (Chemical Engineering Journal, 2025)

Context-dependent allelopathy in algal interactions: Insights from laboratory and natural phytoplankton communities - Kristy S. Syhapanha; Remington X. Poulin; David A. Russo; Wesley Yee Fei Wong; Georg Pohnert (Harmful Algae, 2025)

Cell surface composition, released polysaccharides, and ionic strength mediate fast sedimentation in the cyanobacterium Synechococcus elongatus PCC 7942 - Julie A. Z. Zedler; Marlene Michel; Georg Pohnert; David A. Russo (Environmental Microbiology, 2023)
Cyanobacteria are photosynthetic prokaryotes of high ecological and biotechnological relevance that have been cultivated in laboratories around the world for more than 70 years. Prolonged laboratory culturing has led to multiple microevolutionary events and the appearance of a large number of ‘domesticated’ substrains among model cyanobacteria. Despite its widespread occurrence, strain domestication is still largely ignored. In this work we describe Synechococcus elongatus PCC 7942‐KU, a novel domesticated substrain of the model cyanobacterium S. elongatus PCC 7942, which presents a fast‐sedimenting phenotype. Under higher ionic strengths the sedimentation rate increased leading to complete sedimentation in just 12 h. Through whole genome sequencing and gene deletion, we demonstrated that the Group 3 alternative sigma factor F plays a key role in cell sedimentation. Further analysis showed that significant changes in cell surface structures and a three‐fold increase in released polysaccharides lead to the appearance of a fast‐sedimenting phenotype. This work sheds light on the determinants of the planktonic to benthic transitions and provides genetic targets to generate fast‐sedimenting strains that could unlock cost‐effective cyanobacterial harvesting at scale.

Nitrogen utilization analysis reveals the synergetic effect of arginine and urea in promoting fucoxanthin biosynthesis in the mixotrophic marine diatom Phaeodactylum tricornutum - Runqing Yang; Dong Wei; Georg Pohnert (Frontiers in Marine Science, 2022)
Fucoxanthin is a new dietary ingredient applied in healthy foods with specific benefits of body weight loss and liver fat reduction. The marine diatom Phaeodactylum tricornutum is a highly suitable species for fucoxanthin production. In the present study, aiming to promote fucoxanthin biosynthesis in mixotrophic P. tricornutum , NaNO 3 , tryptone, and urea were evaluated as nitrogen sources with 0.10 mol L −1 of glycerol as the organic carbon source for mixotrophic growth in shake flasks. Compared to NaNO 3 , the mixture of tryptone and urea (referred to as T+U, 1:1, mol N:mol N) as organic nitrogen sources could induce a higher biomass and fucoxanthin production. Through nitrogen utilization analysis, leucine, arginine, lysine, and phenylalanine in the T+U medium were identified as the amino acids that primarily support cell growth. Among those amino acids, arginine causes the highest rate of nitrogen utilization and cell growth promotion. After 12 days of cultivation, the highest biomass concentration (3.18 g L −1 ), fucoxanthin content (12.17 mg g −1 ), and productivity (2.68 mg L −1 day −1 ) were achieved using 25 mmol N L −1 of arginine and 5 mmol N L −1 of urea as nitrogen sources, indicating that arginine and urea performed synergistically on enhancing biomass and pigment production. This study provides new insights into the promotion of fucoxanthin biosynthesis by nitrogen utilization analysis and verifies the synergetic effect of arginine and urea on facilitating the development of a promising strategy for efficient enhancement of fucoxanthin production through mixotrophic cultivation of P. tricornutum .

Pronounced Uptake and Metabolism of Organic Substrates by Diatoms Revealed by Pulse-Labeling Metabolomics - Nils Meyer; Aljoscha Rydzyk; Georg Pohnert (Frontiers in Marine Science, 2022)
Diatoms contribute as a dominant group of microalgae to approximately 20% of the global carbon fixation. In the plankton, these photosynthetic algae are exposed to a plethora of metabolites, especially when competing algae are lysed. It is well established that diatoms can take up specific metabolites, such as vitamins, amino acids as nitrogen source, or dimethylsulfoniopropoionate to compensate for changes in water salinity. It is, however, unclear to which extent diatoms take up other organic resources and if these are incorporated into the cell´s metabolism. Here, we explore the general scope of uptake of metabolites from competitors. Using labeled metabolites released during lysis of algae grown under a 13 CO 2 atmosphere, we show that the cosmopolitan diatom Chaetoceros didymus takes up even dilute organic substrates from these lysates with little bias for molecular weight or polarity. This is reflected by a high degree of labeling in the metabolome of the exposed cells. The newly developed pulse label/mass spectrometry metabolomics approach reveals that polarity and molecular weight has no detectable influence on uptake. We further show that the taken-up metabolites are partly maintained without metabolic modification within the cells, but also a substantial part is subject to catabolic and anabolic transformation. One of the most dominant phytoplankton groups thus has the potential to compete with heterotrophs, suggesting that the observed osmotrophy may substantially impact organic material fluxes in the oceans. Our findings call for the refinement of our understanding of competition in the plankton.

Pheromone Mediated Sexual Reproduction of Pennate Diatom Cylindrotheca closterium - Franziska Klapper; Sien Audoor; Wim Vyverman; Georg Pohnert (Journal of Chemical Ecology, 2021)
Benthic diatoms dominate primary production in marine subtidal and intertidal environments. Their extraordinary species diversity and ecological success is thought to be linked with their predominantly heterothallic sexual reproduction. Little is known about pheromone involvement during mating of pennate diatoms. Here we describe pheromone guided mating in the coastal raphid diatom Cylindrotheca closterium . We show that the two mating types (mt + and mt − ) have distinct functions. Similar to other benthic diatoms, mt + cells are searching for the mt − cells to pair. To enhance mating efficiency mt − exudes an attraction pheromone which we proved by establishing a novel capillary assay. Further, two more pheromones produced by mt − promote the sexual events. One arrests the cell cycle progression of mt + while the other induces gametogenesis of mt + . We suggest that C. closterium shares a functionally similar pheromone system with other pennate diatoms like S eminavis robusta and Pseudostaurosira trainorii which synchronize sexual events and mate attraction. Remarkably, we found no evidence of mt + producing pheromones, which differentiates C. closterium from other pennates and suggests a less complex pheromone system in C. closterium .

High CO 2 concentration and iron availability determine the metabolic inventory in an Emiliania huxleyi ‐dominated phytoplankton community - Michaela A. Mausz; María Segovia; Aud Larsen; Stella A. Berger; Jorun K. Egge; Georg Pohnert (Environmental Microbiology, 2020)
Summary Ocean acidification (OA), a consequence of anthropogenic carbon dioxide (CO 2 ) emissions, strongly impacts marine ecosystems. OA also influences iron (Fe) solubility, affecting biogeochemical and ecological processes. We investigated the interactive effects of CO 2 and Fe availability on the metabolome response of a natural phytoplankton community. Using mesocosms we exposed phytoplankton to ambient (390 μatm) or future CO 2 levels predicted for the year 2100 (900 μatm), combined with ambient (4.5 nM) or high (12 nM) dissolved iron (dFe). By integrating over the whole phytoplankton community, we assigned functional changes based on altered metabolite concentrations. Our study revealed the complexity of phytoplankton metabolism. Metabolic profiles showed three stages in response to treatments and phytoplankton dynamics. Metabolome changes were related to the plankton group contributing respective metabolites, explaining bloom decline and community succession. CO 2 and Fe affected metabolic profiles. Most saccharides, fatty acids, amino acids and many sterols significantly correlated with the high dFe treatment at ambient p CO 2 . High CO 2 lowered the abundance of many metabolites irrespective of Fe. However, sugar alcohols accumulated, indicating potential stress. We demonstrate that not only altered species composition but also changes in the metabolic landscape affecting the plankton community may change as a consequence of future high‐CO 2 oceans.

Author Correction: Attraction Pheromone of The Benthic Diatom Seminavis robusta: Studies on Structure-Activity Relationships - Christine Lembke; Daniel Stettin; Franziska Speck; Nico Ueberschaar; Sam De Decker; Wim Vyverman; Georg Pohnert (Journal of Chemical Ecology, 2019)

Algae induce siderophore biosynthesis in the freshwater bacterium Cupriavidus necator H16 - Colette Kurth; Ina Wasmuth; Thomas Wichard; Georg Pohnert; Markus Nett (BioMetals, 2019)

Attraction Pheromone of The Benthic Diatom Seminavis robusta: Studies on Structure-Activity Relationships - Christine Lembke; Daniel Stettin; Franziska Speck; Nico Ueberschaar; Sam De Decker; Wim Vyverman; Georg Pohnert (Journal of Chemical Ecology, 2018)

Metabarcoding and metabolome analyses of copepod grazing reveal feeding preference and linkage to metabolite classes in dynamic microbial plankton communities - Jessica L. Ray; Julia Althammer; Katrine S. Skaar; Paolo Simonelli; Aud Larsen; Diane Stoecker; Andrey Sazhin; Umer Z. Ijaz; Christopher Quince; Jens C. Nejstgaard; Marc Frischer; Georg Pohnert; et al. (Molecular Ecology, 2016)
In order to characterize copepod feeding in relation to microbial plankton community dynamics, we combined metabarcoding and metabolome analyses during a 22‐day seawater mesocosm experiment. Nutrient amendment of mesocosms promoted the development of haptophyte ( Phaeocystis pouchetii )‐ and diatom ( Skeletonema marinoi )‐dominated plankton communities in mesocosms, in which Calanus sp. copepods were incubated for 24 h in flow‐through chambers to allow access to prey particles ( P. pouchetii , were passively consumed or even negatively selected according to our indicator. Our analysis of the relationship between Calanus grazing ratios and intracellular metabolite profiles indicates the importance of carbohydrates and lipids in plankton succession and copepod–prey interactions. This molecular characterization of Calanus sp. grazing therefore provides new evidence for selective feeding in mixed plankton assemblages and corroborates previous findings that copepod grazing may be coupled to the developmental and metabolic stage of the entire prey community rather than to individual prey abundances.

A solid phase extraction based non-disruptive sampling technique to investigate the surface chemistry of macroalgae - Emilio Cirri; Katharina Grosser; Georg Pohnert (Biofouling, 2016)

Underestimation of microzooplankton grazing in dilution experiments due to inhibition of phytoplankton growth - Diane K. Stoecker; Jens C. Nejstgaard; Rakhesh Madhusoodhanan; Georg Pohnert; Stefanie Wolfram; Hans Henrik Jakobsen; Sigitas Šulčius; Aud Larsen (Limnology and Oceanography, 2015)
Microzooplankton dilution grazing experiments conducted in phytoplankton rich waters, particularly in polar and subpolar seas, often result in calculation of nonsignificant or negative grazing coefficients. We hypothesized that preparation of filtered seawater (FSW) from water containing high biomass of phytoplankton results in release of allelochemicals that inhibit phytoplankton growth, lowering the net growth of phytoplankton in the more diluted treatments. We tested this hypothesis during blooms of Skeletonema marinoi and Phaeocystis pouchetii in a nutrient‐enriched mesocosm in the Raunefjord, Norway. During the S. marinoi bloom, inhibition of phytoplankton growth occurred in the diluted treatments. Simultaneously the concentration of total as well as dissolved polyunsaturated aldehydes (PUAs) was elevated. Passage of the FSW through a carbon cellulose cartridge to remove dissolved organic material reduced, or eliminated, the inhibition. In the early phase of the P. pouchetii bloom that followed the diatom bloom in the mesocosm, PUA concentration was relatively low and the untreated FSW had a less drastic, but often significant, inhibitory effect on phytoplankton growth. Laboratory experiments with cultures of S. marinoi and P. pouchetii confirmed that material present in filtrate prepared from diluted cultures was self‐inhibitory. Many phytoplankters, particularly during late stages of a bloom, produce inhibitory metabolites that may be released during filtration of the relatively large volumes of seawater needed for dilution experiments. Under some conditions, dilution grazing experiments may underestimate phytoplankton growth coefficients and microzooplankton grazing coefficients.

Seasonal fluctuations in chemical defenses against macrofouling in Fucus vesiculosus and Fucus serratus from the Baltic Sea - Esther Rickert; Ulf Karsten; Georg Pohnert; Martin Wahl (Biofouling, 2015)

Sulfation mediates activity of zosteric acid against biofilm formation - Caroline Kurth; Levent Cavas; Georg Pohnert (Biofouling, 2015)

Disruption-free imaging by Raman spectroscopy reveals a chemical sphere with antifouling metabolites around macroalgae - Katharina Grosser; Linda Zedler; Michael Schmitt; Benjamin Dietzek; Jürgen Popp; Georg Pohnert (Biofouling, 2012)

Seaweeds early development: detrimental effects of desiccation and attenuation by algal extracts - Loretto Contreras-Porcia; Sebastián Callejas; Daniela Thomas; Camille Sordet; Georg Pohnert; Aníbal Contreras; Ana Lafuente; María R. Flores-Molina; Juan A. Correa (Planta, 2012)

Extensive cross-disciplinary analysis of biological and chemical control of Calanus finmarchicus reproduction during an aldehyde forming diatom bloom in mesocosms - Sigrún H. Jónasdóttir; Jörg Dutz; Marja Koski; Lidia Yebra; Hans Henrik Jakobsen; Charles Vidoudez; Georg Pohnert; Jens C. Nejstgaard (Marine Biology, 2011)

Up-Regulation of Lipoxygenase, Phospholipase, and Oxylipin-Production in the Induced Chemical Defense of the Red Alga Gracilaria chilensis against Epiphytes - Florian Weinberger; Ulrich Lion; Ludovic Delage; Bernard Kloareg; Philippe Potin; Jessica Beltrán; Verónica Flores; Sylvain Faugeron; Juan Correa; Georg Pohnert (Journal of Chemical Ecology, 2011)

The green alga Dicytosphaeria ocellata and its organic extracts alter natural bacterial biofilm communities - Jennifer M. Sneed; Georg Pohnert (Biofouling, 2011)

The Sesquiterpene Caulerpenyne from Caulerpa spp. is a Lipoxygenase Inhibitor - Sevilay Cengiz; Levent Cavas; Kadir Yurdakoc; Georg Pohnert (Marine Biotechnology, 2011)

No Evidence for the Induction of Brown Algal Chemical Defense by the Phytohormones Jasmonic Acid and Methyl Jasmonate - Theresa Wiesemeier; Karsten Jahn; Georg Pohnert (Journal of Chemical Ecology, 2008)

The potential role of wound-activated volatile release in the chemical defence of the brown alga Dictyota dichotoma: Blend recognition by marine herbivores - Theresa Wiesemeier; Mark Hay; Georg Pohnert (Aquatic Sciences, 2007)

Chemical Defense in Elodea nuttallii Reduces Feeding and Growth of Aquatic Herbivorous Lepidoptera - Daniela Erhard; Georg Pohnert; Elisabeth M. Gross (Journal of Chemical Ecology, 2007)

Lipoxygenase-mediated metabolism of storage lipids in germinating sunflower cotyledons and ?-oxidation of (9Z,11E,13S)-13-hydroxy-octadeca-9,11-dienoic acid by the cotyledonary glyoxysomes - Bernt Gerhardt; Kerstin Fischer; Thomas J. Balkenhohl; Georg Pohnert; Hartmut Khn; Claus Wasternack; Ivo Feussner (Planta, 2005)

Survey of the Chemical Defence Potential of Diatoms: Screening of Fifty Species for α,β,γ,δ-unsaturated aldehydes - Thomas Wichard; Serge A. Poulet; Claudia Halsband-Lenk; Aitor Albaina; Roger Harris; Dongyan Liu; Georg Pohnert (Journal of Chemical Ecology, 2005)

Comparison of the Wound-Activated Transformation of Caulerpenyne by Invasive and Noninvasive Caulerpa Species of the Mediterranean - Verena Jung; Thierry Thibaut; Alexandre Meinesz; Georg Pohnert (Journal of Chemical Ecology, 2002)

Chemical defense of brown algae (Dictyopteris spp.) against the herbivorous amphipod Ampithoe longimana - Iris Schnitzler; Georg Pohnert; Mark Hay; Wilhelm Boland (Oecologia, 2001)

No ecological relevance of trimethylamine in fish— Daphnia interactions - Georg Pohnert; Eric von Elert (Limnology and Oceanography, 2000)
Diel vertical migration (DVM) is a widespread predator‐avoidance behavior in Daphnia and can be induced by kairomones released by fish. It has recently been shown in laboratory experiments that DVM in Daphnia hyalina can be induced by micromolar concentrations of trimethylamine (TMA). The authors concluded, after spectrophotometrical determination of the amine content in fish incubation water, that TMA is an active component of the kairomone. Using a selective solid phase microextraction (SPME)/GCMS method, we show that the TMA content in fish incubation water was overestimated by several orders of magnitude. The amounts of TMA released by any of the three cyprinids Leuciscus idus , Leucaspius delineatus , and Carassius carassius have no relevance for DVM induction and TMA concentrations detected in fish incubation water did not induce DVM. Further, we show that efficient removal of existing TMA traces from fish incubation water did not decrease the kairomone activity. This excludes TMA as part of a kairomone cocktail. Hence TMA must not be called a kairomone in the fish‐ Daphnia context.